2017
DOI: 10.1002/jbmr.3237
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Teriparatide and Recombinant Human Bone Morphogenetic Protein-2 for Regenerative Approach to Medication-Related Osteonecrosis of the Jaw: A Preliminary Study

Abstract: Our objective was to examine whether adjunct teriparatide administration and local application of recombinant human bone morphogenetic protein-2 (rhBMP-2) is beneficial for the regeneration of jaw bone in patients with medication-related osteonecrosis of the jaw (MRONJ). This study enrolled 17 patients diagnosed with MRONJ. All patients received sequestrectomy under general or local anesthesia with suspension of bisphosphonate. The bone regeneration ratio was compared on cone beam computed tomography (CBCT) sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
28
0
16

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 18 publications
0
28
0
16
Order By: Relevance
“…Moreover, a detailed analysis of necrotic bone with empty lacunae, which is one of the important parameters used to assess the severity of MRONJ, was not performed [ 22 ]. Jung et al have reported a clinical preliminary study showing that only transplantation of BMP-2 absorbed with a collagen sponge (BMP-2/collagen) could not significantly induce bone formation at the MRONJ site, compared with the non-transplantation group, and that PTH administration would be necessary to stimulate the effect of BMP-2 in inducing bone formation [ 32 ]. These studies indicate that BMP-2 is an effective growth factor for MRONJ; however, its effectiveness is still suboptimal.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a detailed analysis of necrotic bone with empty lacunae, which is one of the important parameters used to assess the severity of MRONJ, was not performed [ 22 ]. Jung et al have reported a clinical preliminary study showing that only transplantation of BMP-2 absorbed with a collagen sponge (BMP-2/collagen) could not significantly induce bone formation at the MRONJ site, compared with the non-transplantation group, and that PTH administration would be necessary to stimulate the effect of BMP-2 in inducing bone formation [ 32 ]. These studies indicate that BMP-2 is an effective growth factor for MRONJ; however, its effectiveness is still suboptimal.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, however, there is only one animal study that investigated PTH effects on craniofacial fracture healing . In contrast, there have been numerous case reports with positive results for the administration of teriparatide for osseous healing in osteonecrosis of the jaw . Additional investigations will clarify its therapeutic potential for the treatment of maxillofacial fractures and other osseous conditions.…”
Section: Discussionmentioning
confidence: 99%
“…(37) In contrast, there have been numerous case reports with positive results for the administration of teriparatide for osseous healing in osteonecrosis of the jaw. (125)(126)(127)(128)(129) Additional investigations will clarify its therapeutic potential for the treatment of maxillofacial fractures and other osseous conditions.…”
Section: Discussionmentioning
confidence: 99%
“…em seguida, realizou-se uma triagem com a leitura dos títulos e resumos de todos os artigos identificados, para assim excluir os artigos que não atenderam aos critérios de seleção, também foram removidos artigos em duplicata, para então ficarem os artigos para a fase de elegibilidade, nesta fase os artigos foram lidos na íntegra, para mais uma vez, utilizando os critérios de seleção, escolher os artigos agora identificados como artigos incluídos. Para as fases de triagem e de elegibilidade, caso ocorressem conflitos Com os artigos incluídos selecionados, os dados de interesse dos estudos foram extraídos para construção de uma tabela com a síntese das informações mais relevantes à revisão sistemática: nome dos autores, ano de publicação, local de origem da pesquisa; característica da amostra (número total, sexo e idade dos participantes); principal medicação utilizada que induziu a MRONJ e o tempo de uso estimado em anos, com valores convertidos de meses para anos quando necessário; identificação das características dos grupos teste e controle, com o tempo de seguimento da amostra em meses, sendo convertido de semanas para meses quando necessário; e os resultados encontrados referente ao fechamento do defeito ósseo.Sendo um estudo de revisão sistemática não se aplica o cálculo do tamanho da amostra, e em virtude da heterogeneidade encontrada entre os métodos de intervenções utilizados nos estudos, como: diferentes substâncias usadas associadas ao rhBMP-2, havendo o seu uso isolado em apenas um grupo de um só artigo; diferentes tempos de seguimentos das amostras dos estudos incluídos, além disso, os resultados numéricos foram exibidos em gráfico em um dos estudos(Jung et al, 2017), possibilitando identificar apenas valores aproximados dos resultados, por isso, não foram realizados osRESULTADOSForam identificados nas bases de dados 463 publicações: 19 do Pubmed, 01 do LILACS, 339 na Central Cochrane, 51 no Scopus e 53 do Opengrey. Após a triagem dos artigos ficaram 03 estudos, sendo 454 excluídos pelos critérios de seleção e 06 por serem duplicatas; após a leitura na íntegra dos artigos foram selecionados 02 estudos para fazerem parte da revisão sistemática, nestes dois estudos foram buscados nas suas referências novos artigos para serem selecionados, mas das 56 publicações encontradas, nenhuma se enquadrou nos critérios de inclusão e exclusão desta revisão sistemática (Figura 1).…”
unclassified
“…Após a triagem dos artigos ficaram 03 estudos, sendo 454 excluídos pelos critérios de seleção e 06 por serem duplicatas; após a leitura na íntegra dos artigos foram selecionados 02 estudos para fazerem parte da revisão sistemática, nestes dois estudos foram buscados nas suas referências novos artigos para serem selecionados, mas das 56 publicações encontradas, nenhuma se enquadrou nos critérios de inclusão e exclusão desta revisão sistemática (Figura 1). Por outro lado, o s-CTX foi analisado pelos dois estudos incluídos, ficando em média com 0,155ng/mL, quando usado rhBMP-2 + PTH, com 0,202ng/mL exclusivamente fazendo a sequestrectomia e com 0,262ng/mL usando apenas o rhBMP-2(Jung et al, 2017), analisando de modo diferente, Park et al, 2017, demostrou valores maiores ou iguais a 0,15ng/mL para 53,3% no grupo que associou rhBMP-2 + L-PRF e 68% para o uso isolado de L-PRF e valores inferiores a 0,15ng/mL para 46,7% quando usada a associação entre rhBMP-2 + L-PRF e 32% para o uso isolado de L-PRF, entretanto, sem também haver para estas variáveis resultados significantes.…”
unclassified